ANALISIS DAMPAK INDUSTRI TERHADAP POLUSI UDARA (STUDI KASUS INDUSTRI MINYAK DAN GAS BUMI DI KABUPATEN TANGGAMUS LAMPUNG) - Aurel Rani Avidesta R; Dela Eka Sasputri, M Rafiudin Safikri, Alva Yenica Nandavita (BORJUIS: JURNAL OF ECONOMY, 2025)
The oil and gas industry plays an important role in the economy, but on the other hand, its activities have the potential to pollute the environment, particularly air quality. This study aims to analyze the impact of the oil and gas industry on air pollution in Tanggamus Regency, Lampung. The study was conducted by collecting primary data through air quality measurements around the industrial area and interviews with the community and industry workers. In addition, secondary data regarding industrial activities and environmental management policies were also analyzed. The research findings show that oil and gas exploitation activities in Tanggamus lead to an increase in the concentration of dust particles and emissions of harmful gases in the air, such as carbon monoxide (CO) and nitrogen oxides (NOₓ), which pose a risk to public health and environmental quality. The study also found that despite some mitigation efforts, air pollution management still needs to be strengthened to minimize negative impacts on ecosystems and human health. The recommendations include improving environmentally friendly technology, stricter monitoring, and implementing more effective policies for controlling air pollution.